Female Body Anthropometric Variation and Breakthrough in Anthropology for Digital Modelling - Badriatut Dini; M. R. Hutagalung; D. S. Perdanakusuma; Phill T Koesbandriati; Agus Windharto (Institut Teknologi Sepuluh Nopember, 2014)
Plastic reconstructive and aesthetic surgery has emerged to meet the challenge of improving body size and shape. Currently, body reconstruction in Indonesia refers to Caucasian parameters which may not be applicable. Moreover, patients cannot comprehend the surgeon’s prediction of the surgical outcome visually making it more difficult for the surgeon to describe the operative result. Reseach Objective is understanding the supernormal body concept in Indonesia, describing variation of normal and supernormal body indexes of Indonesians as a formulation base and to make a 3D digital modeling of normal and supernormal person. These models will be used as guidance for planning and predicting the reconstruction - aesthetic surgery in body contouring and as assisting tool for giving information visually to patients. Reseach method using applied study. Questionnaires were distributed to a hundred male and female adults respondent to obtain the concept of Indonesian normal and supernormal bodies. The Body model are 17-25 years old and then divided into 2 groups, normal and supernormal by expert juries assessment. The data of body index anthropometry were presented in tables, charts, and narration to describe normal and supernormal morphologic variations, then results between the 2 groups were compared statistically by t-test and discriminant test. Anthropometric and photographic data were used for making normal and supernormal 3D digital woman models. Criteria of body attractiveness by questionnaire were bright skin color, tallness, slimness, hour glass body shape, muscular arms, medium sized shoulders, hip, waist, breasts and buttocks, wide chest and slender legs. There were significant differences in body measurement between normal-supernormal and distinguishing parameters between normal -supernormal groups by discriminant test including chest dimension index, waist hip ratio, triceps skinfold and leg length. There were two 3D digital woman models for both normal and supernormal subjects which had measurements approximating the average values of each group.